Long Non-coding RNAs: Major Regulators of Cell Stress in Cancer - Connerty, Patrick; Lock, Richard B.; de Bock, Charles E. (Frontiers in Oncology, 2020)
Cellular stress can occur in many forms; oxidative stress caused by reactive oxygen species (ROS), metabolic stress from increased metabolic programs and genotoxic stress in the form of DNA damage and disrepair. In most instances, these different types of cell stress initiate programmed cell death. However, in cancer, cells are able to resist cellular stress and by-pass growth limiting checkpoints. Recent findings have now revealed that the large and heterogenous RNA species known as long non-coding RNAs (lncRNAs) are major players in regulating and overcoming cancer cell stress. lncRNAs constitute a significant fraction of the genes differentially expressed in response to cell stress and contribute to the management of downstream cellular processes, including the regulation of key stress responses such as metabolic stress, oxidative stress and genotoxic stress. This review highlights the complex regulatory role of lncRNAs in the cell stress response of cancer by providing an overview of key examples from recent literature.